Mediatization of religion in “texting culture”: self-help religion and the shifting of religious authority - Moch Fakhruroji (IAIN Salatiga, 2015)
This research is the study of SMS Tauhiid phenomena as a religious practicein the context of media culture. SMS Tauhiid service enables its customer toaccess religious messages through SMS which is in particular contexts couldpotentially bring new patterns of religious practice. This article uses themediatization concept dealing with media studies and political economy aswell. I argue that tausiah as (Islamic) religious communication practice havetransformed into a new pattern that caused by the accomodative actions thathas taken by the religious leaders and actors against media logics. On the onehand, this phenomenon has opened a new phase in disseminating religiousmessages, however on the other hand mediatization of religion has potentialin causing a shift in the role of religious leaders as the religious authorities.Penelitian ini merupakan studi tentang fenomena SMS Tauhiid sebagai bentukpraktik agama dalam konteks budaya media. SMS Tauhiid memungkinkansetiap pelanggan dapat mengakses nasihat agama melalui SMS yang dalamkonteks tertentu berpotensi memunculkan pola-pola baru dalam beragama.Artikel ini menggunakan pendekatan konsep mediatisasi yang memiliki kaitanerat dengan disiplin media studies dan ekonomi politik. Saya berargumen bahwa tausiah sebagai praktik komunikasi agama (Islam) telah mengalamitransformasi kedalam bentuk baru disebabkan tindakan akomodatif yangdilakukan para tokoh dan aktor agama terhadap logika media. Di satu sisi,fenomena ini telah membuka babak baru bagi proses penyebaran pesan-pesanagama, namun di sisi lain mediatisasi berpeluang menyebabkan pergeseranperan tokoh agama sebagai pihak yang memiliki otoritas sumber informasiagama.